EFFECT OF SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) ON THE HIGHER ORDER THINKING SKILL (HOTS) OF ELEMENTARY SCHOOL STUDENTS - Utaminingsih, Sri; Nooryanti, Suci; Su'ad; Ermawati, Diana (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
The Science, Technology, Engineering, and Mathematics (STEM) learning model is an effective approach to improving 21st-century skills. Several studies have shown that this model is able to develop students' Higher Order Thinking Skills (HOTS), learning outcomes, creativity, and innovation. This study is a quantitative study with a quasi-experimental design, using a non-equivalent pretest–posttest control group design. The sampling technique used was simple random sampling. The study population included all fifth-grade students in Mejobo Regency spread across 46 elementary schools. The study sample consisted of 34 fifth-grade students of SD 5 Jepang and 35 fifth-grade students of SD 1 Kasil as the experimental class, and 31 fifth-grade students of SD 2 Jepang as the control class. Data collection techniques included interviews, tests, and documentation. The results of the analysis showed that the implementation of the STEM learning model had a positive effect on students' HOTS abilities, with a t-test value of 2.9 > t-table 2.0 and an average score increase of 58.9%. Based on the results of this study, it can be concluded that the STEM learning model has a significant effect on improving the high-level thinking skills of fifth-grade elementary school students.